2003
DOI: 10.1002/chin.200343112
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Aminobenzothiazoles from 2,3‐Biaryl‐5‐anilino‐Δ3‐1,2,4‐thiadiazolines.

Abstract: Benzothiazole derivatives Benzothiazole derivatives R 0270The Synthesis of Aminobenzothiazoles from 2,3-Biaryl-5-anilino-∆ 3 -1,2,4-thiadiazolines. -2,3-Biaryl-5-anilino-∆ 3 -1,2,4-thiadiazolium bromides (I) undergo a thermally-promoted rearrangement forming 2-amidinobenzothiazoles (II). In some cases, the yield can be improved by adding a base. -(PAN*, K.; REITZ, A. B.; Synth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The stability and reactivity of other thiadiazoles have been studied by several authors. Pan et al have demonstrated that thiadiazoles bearing aryl R 2 substituents shown to be active as melanocortin MC4 receptor agonists may undergo a thermal rearrangement to 2-amidinobenzothiazole in DMSO. , The same authors reduced 2-(4-methylphenyl)-3-phenyl-5-(4-methoxyphenylamino)-[1,2,4]-thiadiazolium bromide to its precursor imidoylthiourea by dithioerythritol. They suspected that this compound also reacts with the thiol group on cysteine residues or that it oxidizes two thiol groups to create a disulfide bond, causing irreversible binding to the receptor .…”
Section: Resultsmentioning
confidence: 99%
“…The stability and reactivity of other thiadiazoles have been studied by several authors. Pan et al have demonstrated that thiadiazoles bearing aryl R 2 substituents shown to be active as melanocortin MC4 receptor agonists may undergo a thermal rearrangement to 2-amidinobenzothiazole in DMSO. , The same authors reduced 2-(4-methylphenyl)-3-phenyl-5-(4-methoxyphenylamino)-[1,2,4]-thiadiazolium bromide to its precursor imidoylthiourea by dithioerythritol. They suspected that this compound also reacts with the thiol group on cysteine residues or that it oxidizes two thiol groups to create a disulfide bond, causing irreversible binding to the receptor .…”
Section: Resultsmentioning
confidence: 99%